Estimation of Credible Net Premiums by World Regions to Cover Catastrophe Losses - Jindrová, Pavla (My University, 2017)
The number of catastrophic events and the amount of economic losses is varying in different world regions. Part of these losses is covered by insurance. Catastrophic events in last years are associated with increases in premiums for some lines of business. The aim of this article is determination of estimates of the net premiums that would be needed to cover total or insured catastrophic losses in different world regions. For these estimates Bühlmann and Bühlmann-Straub empirical credibility models based on data from Sigma Swiss Re 2010-2016 are used. The empirical credibility models have been developed to estimate credibility premium or insurance premium for short term insurance contracts using two ingredients: past data from the risk itself and collateral data from other sources considered to be relevant. In this article we deal with application of these models based on the real data about number of catastrophic events and about the total economic and insured catastrophe losses in seven regions of the world in time period 2009-2015. Our significant results of estimated credible premiums by world regions provide information about how much money in these regions will be need to cover total or insured catastrophic losses in the next year.
Kredibilní odhady čistého pojistného k pokrytí katastrofických škod ve světových regionech
Keywords: Empirical credibility model; economic losses; insured losses; net premium; world regions.; Empirický model kredibility; ekonomické škody; pojištěné škody; světové regiony.